HUBUNGAN KAPASITAS PARU TERHADAP FAKTOR INDIVIDU DAN LINGKUNGAN PADA PEKERJA UNIT WEAVING BAGIAN LOOM 1 DAN LOOM 3 PERUSAHAAN TEKSTIL X TAHUN 2016 - Laksana, Ni'matun Faizah; Jayanti, Siswi; Kurniawan, Bina; Suwondo, Ari (Jurnal Kesehatan Masyarakat (e-Journal), 2017)
The textile industry has a high risk of lung capacity disruption due to high exposure of cotton dust during the production process. Work environment and individual factors can increase the risk. This research aimed to analyze the differences in lung capacity of machine operator loom 1 and loom 3 also identify the factors that influence. This research used explanatory research method with cross sectional approach. Total population of the research was 166. Samples in this research are 26 machine operators loom 1 and 39 machine operator loom 3 â€œXâ€ textile company. Identifying correlation using Chi-Square and Fisher's Exact Test, difference analysis using Mann Whitney Test. The results showed that no differences between the mean lung capacity in parts loom 1 and loom 3 (p = 0.674). The result on loom 1, there is relationship between age (p = 0.016) with the lung capacity, and there is no relationship between the work period (p = 0.617), nutritional status (p = 1.000), history of disease (p = 0.189), and wearing masks (p = 0.538) with the lung capacity. The result on loom 3 there is relationship between history of the disease (p = 0.001) and wearing masks (p = 0.002) with the lung capacity, and there is no relationship between age (p = 0.068), age (p = 0.253), and nutritional status (p = 0.725) with the lung capacity.